Research progress of leachate treatment in waste transfer station - Fu Yuan; Su Dexin; Ma Sai; Xiao Yan (E3S Web of Conferences, 2024)
The garbage leachate generated by the waste transfer station has the characteristics of scattered water sources, relatively small water quantity, large fluctuations in water quality and quantity, and high concentrations of organic matter, ammonia nitrogen, suspended solids, and other pollutants. These characteristics make it prone to environmental hazards. This paper analyzes the characteristics and hazards of leachate from waste transfer stations and introduces the current research status of physico-chemical, biological, and combined treatment of leachate from waste transfer stations. Meanwhile, this paper introduces engineering practices for leachate treatment in waste transfer stations, offering a valuable reference for research and engineering practices in this field. Finally, this review discusses pretreatment, economic, low-carbon, and high-efficiency treatment methods and facilities, the recovery of valuable elements, energy recycling technologies, and the demand outlook for high-standard deep treatment processes.